Manual for the design of plain masonry in building structures to Eurocode 6. (The Institution of Structural Engineers, 2018)
"This Manual provides guidance on the design of loadbearing masonry and masonry infill to structural frames ... The Manual covers structural fire design of masonry and selection of materials and execution of masonry. Established good practice not covered in the Eurocodes is included, and suitably identified."--Page xiii.